Factors associated with decision-making power of married women to use family planning in sub-Saharan Africa: a multilevel analysis of demographic health surveys - Getu Debalkie Demissie; Yonas Akalu; Abebaw Addis Gelagay; Wallelign Alemnew; Yigizie Yeshaw (BMC, 2022)
Abstract Background In sub-Saharan Africa, there are several socio-economic and cultural factors which affect women's ability to make decision regarding their own health including the use of contraceptives. Therefore, the main aim of this study was to determine factors associated with decision-making power of married women to use family planning service (contraceptives) in sub-Saharan Africa. Methods The appended, most recent demographic and health survey datasets of 35 sub-Saharan countries were used. A total weighted sample of 83,882 women were included in the study. Both bivariable and multivariable multilevel logistic regression were done to determine the associated factors of decision-making power of married women to use family planning service in sub-Saharan countries. The Odds Ratio (OR) with a 95% Confidence Interval (CI) was calculated for those potential variables included in the final model. Results Married women with primary education (AOR = 1.24; CI:1.16,1.32), secondary education (AOR = 1.31; CI:1.22,1.41), higher education (AOR = 1.36; CI:1.20,1.53), media exposure (AOR = 1.08; CI: 1.03, 1.13), currently working (AOR = 1.27; CI: 1.20, 1.33), 1-3 antenatal care visits (AOR = 1.12; CI:1.05,1.20), ≥ 4 ANC visits (AOR = 1.14;CI:1.07,1.21), informed about family planning (AOR = 1.09; CI: 1.04, 1.15), having less than 3 children (AOR = 1.12; CI: 1.02, 1.23) and 3-5 children (AOR = 1.08; CI: 1.01, 1.16) had higher odds of decision-making power to use family planning. Mothers who are 15-19 (AOR = 0.61; CI: 0.52, 0.72), 20-24 (AOR = 0.69; CI: 0.60, 0.79), 25-29 (AOR = 0.74; CI: 0.66, 0.84), and 30-34 years of age (AOR = 0.82; CI: 0.73, 0.92) had reduced odds off decision-making power to use family planning as compared to their counterparts. Conclusion Age, women's level of education, occupation of women and their husbands, wealth index, media exposure, ANC visit, fertility preference, husband's desire in terms of number of children, region and information about family planning were factors associated with decision-making power to use family planning among married women.